PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENTS-TEAM ACHIEVEMENT DIVISIONS) UNTUK MENINGKATKAN KEMAMPUAN SISWA DALAM MEMPRESENTASIKAN LAPORAN PENELITIAN SEJARAH LOKAL PADA KELAS XI TKJ 1 SMK NEGERI I BANAWA KABUPATEN DONGGALA - Ajezun, Ajezun (Katalogis, 2016)
This classroom action research applies cooperative learning model of STAD. Its aim is to know whether the application of cooperative learning model of STAD can increase the students’ ability in presenting a local history research report. The subject is the students of TKJ 1 consisting of 40 students, 15 girls and 25 boys. The procedures follow the cycle consisting of planning, acting, observing, and analysing and reflecting. This research is carried out in 2 cycles, cycle 1 consisting of 4 meetings and cycle 2 concisting of 3 meetings. Every meeting implements the procedures of learning model of STAD. Data is collected through the result of quiz, the students’ group presentation, observation sheets, and discussion. In cycle 1 the result of observation sheet to the students’ activities show that the students’ achievements are around point 1 and 2 (not yet appear and already appear). This influences the students’ achievement either in the quiz or in the presentation of the groups’ research report . The quiz result is 80.05% and the result of students’ group presentation reach only 66,67% to 83,33%, meaning that the average is 72,91%. The achievement does not reach the criteria of succeess, consequently the research is continued to cycle 2. In cycle 2, there is a significant change to the result of the students’ groups’ presentation. The achievement is 86,45%. It is supported by the result of the observation on the students’ activities. It reaches 3 and 4 (develop and accustomed) or the percentage is 95%. The result of quiz reaches 93,2%. These show that the application of the cooperative learning model of STAD can increase the students’ ability in presenting a local history research report.